Obras humanas e exigências naturais : a significação do homem no seio da natureza em Gabriel Tarde e Henri Bergson - Teixeira, Rafael Henrique (2015)
This thesis analyses the affinities between Gabriel Tarde's and Henri Bergson's philosophies of nature, focusing on their ideas about the man’s meaning, place and role among the works of nature. I will draw from a double shared postulate : Firstly the admission that a nature, which is creative, fulfills well-defined requirements on the act of creation. Throughout the entire nature we will find an effort of creation operating, which is the source of every one of its products, from matter to man. Secondly the evidence that these products extend the requirements in which they find their purpose or reason of existence with more or less success. Once having discriminated the series of beings which emerges from that great enterprise of creation, Tarde and Bergson locate the man at its crown. This man will be described at the same time as one of its products tied to all that forego his dawn and, as an exceptional one, the product in which will be possible for nature to find a solution to its primordial requirements of creation in an exceptional successful way. Nevertheless this man emerged from the general movement of nature, and by prolonging requirements that are preanthropological, will not be made an immediately absolute success only by the exercise of his freedom, sociability and inventiveness. It will be required the action of exceptional individuals who, dragging humanity by their example, will solve the contradictions that nature's inventive genius just relatively evaded. These individualities will be the mystics that accomplish an analogous role in both Tarde's and Bergson's works. Yet, I will carefully demonstrate that despite these affinities we are not allowed to state a full parallelism between Tardian and Bergsonian developments. According to Tarde the effort that we find throughout nature is an effort of progressive harmonization which seeks to place in agreement one pulsive multiplicity that makes background to what is regular in the universe. According to Bergson it consists on an effort to introduce indeterminacy in the universe of necessity, work achieved by the evolution of the living world that creates organisms whose actions will fight against the inertia of matter.To the former, nature appears as a great compositional plan in which matter, life and man figures as stages in a process that leads to progressively comprehensive harmonies. To the latter, a cosmology which deals with the integration between the cosmos strata is inseparable from a philosophy of life and even from a sui generis biological transfomism. Instead of well-delimited stages, Bergson presents life and matter as tendencies that contradict themselves, from whose clash results the whole organized world and, inside its limits, the humankind as one of the solutions that life found when it has converted the matter, obstacle at first, to instrument.